1998
DOI: 10.1021/jp980238y
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemistry and Extreme-Pressure Lubricant Properties of Dimethyl Disulfide

Abstract: The growth kinetics of a film formed by the thermal decomposition of dimethyl disulfide on an iron foil are measured using a microbalance where the growth kinetics are parabolic (film thickness X varies with time as X 2 ∝ t) at high reaction temperatures and pressures, indicating that it is limited by diffusion through the film. The activation energy for this process is 54.5 ( 0.5 kcal/mol. The growth rate becomes linear as the reaction temperature and/or reactant pressure is lowered, indicating that, under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…The experiments in this work were carried out using DMDS, and sulfur-containing molecules are used as lubricant additives [16,17]. Since rubbing results in the formation of a metastable film and the regeneration of a clean surface, this is available to adsorb more DMDS, which will then be tribologically transported into the subsurface region; repetition of this process will result in the formation of a sulfur-containing film.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments in this work were carried out using DMDS, and sulfur-containing molecules are used as lubricant additives [16,17]. Since rubbing results in the formation of a metastable film and the regeneration of a clean surface, this is available to adsorb more DMDS, which will then be tribologically transported into the subsurface region; repetition of this process will result in the formation of a sulfur-containing film.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally agreed that AW films containing a relatively hard polyphosphate glass are formed by reaction with the phosphorus in the additive. Chlorine- [8,9], sulfur- [10,11] and phosphorus-containing [12][13][14][15][16] molecules are all used as EP additives. It has been demonstrated previously that chlorinated hydrocarbons function by reactively forming a FeCl 2 film [17][18][19] at the high temperatures (>1000 K [20]) encountered at the solid-solid interface during EP applications.…”
Section: Introductionmentioning
confidence: 99%
“…Further, considering that there is only a very small amount of C found on the slid surface in stage I, we argue that the antioxidant is readily available to be adsorbed on the iron surface to form, initially, thiolates by cleavage of the SÀS bond and then FeS when the CÀS bond is cleaved. 21,22 Table 1 shows that the sulfur concentration increases with time in stage I. It may be suggested that hydrocarbon aging plays no role in stage I wear.…”
Section: Resultsmentioning
confidence: 99%